2013
DOI: 10.1016/j.anifeedsci.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous enzymes on in vitro gas production kinetics and ruminal fermentation of four fibrous feeds

Abstract: a b s t r a c tThis study was conducted to investigate effects of increasing doses: 0 (control), 6 (low), 12 (medium) and 24 (high) mg/g DM of ZADO ® enzyme preparation mixture (ENZ) on in vitro gas production (GP) and some ruminal fermentation parameters of the fibrous feeds Saccharum officinarum (leaves), Andropogon gayanus (leaves), Pennisetum purpureum (leaves) and Sorghum vulgare (straw). Rumen liquor was obtained from two Brown Swiss cows fitted with permanent rumen cannulae fed a total mixed ration of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 27 publications
4
45
0
1
Order By: Relevance
“…The addition of fibrolytic enzymes facilitates the access of microorganisms to feed components enabling a faster microbial growth. Gas production during the first hours of ruminal fermentation was increased in the present study, supporting the hypothesis that a suitable ENZ level could improve the fermentation of feeds during the initial stages of forage digestion (Elghandour et al 2013). Diaz et al (2013) observed that the addition of a fibrolytic enzyme increased the fermentation rate of maize stover, although asymptotic GP was unaffected.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The addition of fibrolytic enzymes facilitates the access of microorganisms to feed components enabling a faster microbial growth. Gas production during the first hours of ruminal fermentation was increased in the present study, supporting the hypothesis that a suitable ENZ level could improve the fermentation of feeds during the initial stages of forage digestion (Elghandour et al 2013). Diaz et al (2013) observed that the addition of a fibrolytic enzyme increased the fermentation rate of maize stover, although asymptotic GP was unaffected.…”
Section: Discussionsupporting
confidence: 75%
“…Elghandour et al (2013) observed that the amount of enzyme added to different fibrous feeds has a positive effect on in vitro nutrient digestibility. Lara-Bueno et al (2013) reported a greater disappearance in situ for DM and NDF after 24 and 48 h of incubation of oat straw treated with a fibrolytic enzyme.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These variations arise from variation in the genotype of the crops, differences between production environments, and from the interaction between environment and genotypes (Welch, 1995;Denčić et al, 2011). Environmental differences will include variation in climate, the soil and agronomic practice, together with variations raised from different harvesting conditions, and post harvesting treatments (Welch, 1995;Elghandour et al 2013). There is usually an inverse relationship between the CP and crude fibre content in a given forage species, and this has been revalidated in this study.…”
Section: Chemical Compositionmentioning
confidence: 99%